fullsimplify problem

*To*: mathgroup at smc.vnet.net*Subject*: [mg52908] fullsimplify problem*From*: "symbio" <symbio at has.com>*Date*: Thu, 16 Dec 2004 03:41:11 -0500 (EST)*Reply-to*: "symbio" <symbio at sha.com>*Sender*: owner-wri-mathgroup at wolfram.com

Given ( - a / b^2) = = ( + a / b^2), it can be written as (-2 a / b^2), but when I use FullSimplify on that equation, I get the incorrect result ( a / b ) = = 0. How is this possible? In[2]:= -a/b^2 == a/b^2 % // FullSimplify Out[2]= \!\(\(-\(a\/b\^2\)\) == a\/b\^2\) Out[3]= \!\(a\/b == 0\) In[5]:= -2a/b^2 == 0 // FullSimplify Out[5]= \!\(a\/b == 0\)

**Follow-Ups**:**Re: fullsimplify problem***From:*DrBob <drbob@bigfoot.com>